2017
DOI: 10.1021/acs.langmuir.7b03093
|View full text |Cite
|
Sign up to set email alerts
|

Propane–Water Mixtures Confined within Cylindrical Silica Nanopores: Structural and Dynamical Properties Probed by Molecular Dynamics

Abstract: Despite the multiple length and time scales over which fluid-mineral interactions occur, interfacial phenomena control the exchange of matter and impact the nature of multiphase flow, as well as the reactivity of C–O–H fluids in geologic systems. In general, the properties of confined fluids, and their influence on porous geologic phenomena are much less well understood compared to those of bulk fluids. We used equilibrium molecular dynamics simulations to study fluid systems composed of propane and water, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 66 publications
5
39
0
Order By: Relevance
“…To fill the gaps in our understanding of the behavior of coexisting water and a volatile, we report here a quasielastic neutron scattering (QENS) study on the effect of D2O on the dynamics of propane confined in MCM-41-S at low temperatures (230 and 250 K). The results of these experiments are complemented by MD simulations, which build our previously reported simulation studies 35 . Both experiment and simulations suggest that water hinders the diffusion of propane in MCM-41-S pores.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…To fill the gaps in our understanding of the behavior of coexisting water and a volatile, we report here a quasielastic neutron scattering (QENS) study on the effect of D2O on the dynamics of propane confined in MCM-41-S at low temperatures (230 and 250 K). The results of these experiments are complemented by MD simulations, which build our previously reported simulation studies 35 . Both experiment and simulations suggest that water hinders the diffusion of propane in MCM-41-S pores.…”
Section: Introductionmentioning
confidence: 79%
“…The preparation of the simulation cell used in this work has been described elsewhere 35 . It consisted of two stagespreparing a cylindrical pore of amorphous silica, and then loading water and propane molecules in this pore.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[81][82] The system was simulated as confined within a realistic cylindrical pore of diameter ~16 Å carved out of amorphous silica. A detailed description of the procedure implemented during the preparation of the cylindrical silica pore has been presented in a previous study, 83 in which we studied the transport properties of confined water-propane systems, using non-reactive force fields. In Figure 1A, we provide a schematic of the pore, which is found within a 57.28 Å x 57.28 Å x 57.28 Å simulation box with periodic boundary conditions along the 3 directions.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…With more than 80% of our energy needs being met by the subsurface environments (BP Global, 2015), there is a significant interest in environmentally benign approaches to recover and store fluids in complex materials characterized by chemical and morphological heterogeneity and nano-scale porosity. Various studies have shown that the properties and transport of confined fluids such as water (Bonnaud et al, 2010;Ho and Striolo, 2015;Hu et al, 2015;Chakraborty et al, 2017), gases such as CO 2 (Chialvo et al, 2012;Striolo and Cole, 2017;Simoes Santos et al, 2018), and hydrocarbons (Cole et al, 2013;Le et al, 2015a,b;Wu et al, 2015;Le T. T. B. et al, 2017;Herdes et al, 2018;Obliger et al, 2018;Simoes Santos et al, 2018) in nanoporous environments differs from bulk behaviors due to changes in the structure and affinity of confined liquids (Wang H. et al, 2016;Johnston, 2017) and gases (Yuan et al, 2015;Sun et al, 2016aSun et al, ,b, 2017Wang S. et al, 2016a,b) for the solid interfaces. With increasing interest in enhanced gas recovery coupled with subsurface CO 2 storage, a fundamental understanding of the changes in the structure of CO 2 and CH 4 and transport properties of these gases through water-bearing nanoporous environments provides a scientific basis for the observed fate and transport of these gases at the field scale (Glezakou and McGrail, 2013;Gadikota et al, 2017;Gadikota, 2018;Gadikota and Allen, 2018).…”
Section: Introductionmentioning
confidence: 99%